TEACHING VOCABULARY USING WORDWALL - Jenny Erza; Urai Salam; Luwandi Suhartono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examined the use of Wordwall as a digital tool to improve vocabulary learning and student engagement among seventh-grade students of SMPN 29 Pontianak in the academic year 2024/2025. Conducted through Classroom Action Research (CAR) in two cycles, data were collected using several instruments, namely vocabulary tests to measure students’ vocabulary mastery, observation checklists to monitor classroom activities and engagement, and questionnaires to capture students’ perceptions and responses. The findings showed a clear improvement in students’ vocabulary achievement, with the mean score rising from 57.64 in Cycle I to 88.27 in Cycle II. Wordwall supported this progress through interactive activities such as matching games, word searches, and sentence completion, which provided repeated exposure, feedback, and meaningful practice. Students also responded positively, showing greater motivation, enthusiasm, and participation during lessons. In conclusion, integrating Wordwall not only improved vocabulary outcomes but also fostered a more engaging and motivating classroom environment, highlighting its potential as a useful tool in English vocabulary instruction.